(untitled) (Journal of Pharmaceutical Negative Results, 2023)
As the banking business has become more competitive, banks must be more strategic in order to satisfy the increased demands of their customers. The secret to attracting and retaining consumers, it is said, is in the effective management of client relationships. The study's goal is to determine how relationship marketing dimensions affect customer satisfaction in the banking industry. Data from 203 bank clients was gathered via questionnaires in order to accomplish the study's goal. The study's key conclusions highlight the considerable impact relationship marketing strategies have on the quality of relationships and client happiness. The research also shows that the strength of a connection has a big impact on customer satisfaction. According to the findings, banks that want to have good relationships with their customers should insist that “managers and employees act trustworthily, competently, and with a strong commitment to providing excellent customer service”. They should also require that they communicate clearly and dependably, pay close attention to shared values, and work to improve the quality of relationships with customers.